The The Phylogenetic Analysis of Parmarion Martensi Simroth, 1893 Collections Of The Museum Zoologicum Bogoriense From Java Based On Cox1 Gene - Prasetia, Ahmad Ghifari; Hermawan, Wawan; Nurinsiyah, Ayu Savitri (Masyarakat Moluska Indonesia, 2025)
Parmarion martensi Simroth, 1893 is a snail a reduction of shell and often known as semislug. The species is distributed from Southeast Asia to the Hawaian Archipelago. There are two species of Parmarion in Java which can be distinguished only from the genitalia. This study was conducted to reveal the phylogenetic and genetic distance of P. martensi in Java based on the COX1 gene with K2P genetic pairwise distance, mrbayes, and IQtree analysis. The analysed specimens were the scientific collections of the Museum Zoologicum Bogoriense. We used two specimens from the GenBank for comparison, and three specimens as outgroup . The phylogenetic analysis resulted three clades i.e., clade A as consist of Microparmarion from Borneo as semi-slug outgroup, clade B consist of P. martensi from Java, and clade C consist of P. martensi from Taiwan. P. martensi has a polytomy relationship between P. martensi Java and Taiwan. Beside that, P. martensi Java also has a polytomy relationship between West Java and East Java species with statistical support (PP = 93; BS = 51). Then, genetic distance between P. martensi Java have genetic distance around 0 – 4,64 %, whereas genetic distance between P. martensi Java and Taiwan have a high genetic distance around 5.89 – 10.18%. In this case, P. martensi has a high threshold on the COX1 gene around 0 – 10.18% as the same species.